2013
DOI: 10.1371/journal.pone.0065148
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Induced Changes in the Proteome of Trichomonas vaginalis Hydrogenosomes

Abstract: Iron plays a crucial role in metabolism as a key component of catalytic and redox cofactors, such as heme or iron-sulfur clusters in enzymes and electron-transporting or regulatory proteins. Limitation of iron availability by the host is also one of the mechanisms involved in immunity. Pathogens must regulate their protein expression according to the iron concentration in their environment and optimize their metabolic pathways in cases of limitation through the availability of respective cofactors. Trichomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 38 publications
4
77
0
1
Order By: Relevance
“…The TvIsf paralog herein named TvIsf3 was selected for our study because its presence in hydrogenosomes was confirmed by two independent proteomic studies (19,20) and because our previous analysis revealed that the mRNA of this gene was produced at the highest level of all seven TvIsf paralogs (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TvIsf paralog herein named TvIsf3 was selected for our study because its presence in hydrogenosomes was confirmed by two independent proteomic studies (19,20) and because our previous analysis revealed that the mRNA of this gene was produced at the highest level of all seven TvIsf paralogs (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ferredoxin and not the pyridine nucleotide coenzyme was identified as an electron donor to Isf from Methanosarcina for the reduction of oxygen and hydrogen peroxide (6). T. vaginalis encodes seven paralogs of ferredoxin (18), and most of them, if not all, are expressed in the hydrogenosomes (19,20), where they serve as one-electron carriers that link the crucial reactions of hydrogenosomal metabolism (10). Ferredoxin is an electron donor to the oxygen-reducing and water-forming flavodiiron protein (17); in this work, we show that upon in vitro reduction by hydrogenosomal PFO, ferredoxin can also transfer electrons to TvIsf3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is indicative of the self clearing nature of the infection in males, with the majority of persistent infections occurring in females (Van Der Pol, 2007). The higher likelihood of persistence in the female genital tract has been linked to the availability of iron, which increases during the menstrual cycle, providing the parasite with increased exposure to a major growth requirement (Beltrán et al, 2013). The expression of various adhesion proteins promoting cytoadherance is enhanced in response to increased iron concentration (Sehgal et al, 2012), and this is associated with increased virulence (Ryu et al, 2001).…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%